SOCIAL, ECONOMIC, AND CULTURAL ANALYSIS IN THE PREPARATION OF AMDAL ON THE LICENSING ACTIVITIES OF FOREST UTILIZATION BUSINESS (PBPH) IN THE PRODUCTION FOREST OF PT. PUTRA BARITO LESTARI - Abdurrahman; Hidayatullah; Muhammad Viki Firdaus (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2024)
The activity plan for the utilization of wood forest products in natural forests in production forests by PBPH PT. Putra Barito Lestari is administratively located in Katingan Tengah, Katingan Hilir, Tasik Payawan and Kamipang Districts, Katingan Regency, Central Kalimantan Province. The land cover conditions at the planned activity location of PT. Putra Barito Lestari consist of Swamp Scrub, Secondary Dryland Forest, Secondary Swamp Forest, Plantation, Mining, Shrub/Scrub, Swamp, and Open Land. In general, the activity plan for Forest Utilization Business Licensing (PBPH) in production forests by PT. Putra Barito Lestari is divided into 4 (four) stages of activity, namely the pre-construction, construction, operation and post-operation stages. This study uses an interview survey method where the data obtained is primary data from interviews in the field (in situ) and secondary data is taken from the BPS of Katingan Regency. There are 10 discussions in SOCIAL, ECONOMIC, AND CULTURAL ANALYSIS IN PREPARING AMDAL ON FOREST UTILIZATION BUSINESS LICENSING ACTIVITIES (PBPH) IN PRODUCTION FORESTS OF PT. PUTRA BARITO LESTARI Namely population, Livelihoods and Employment, Community Income Level, Community Expenditure Level, Land Ownership and Control, Facilities and Infrastructure, Customs and Habits, Social Processes, Community Attitudes and Perceptions, and Community Unrest and Potential Conflict. The results of Interview Observations in the community in Katingan Tengah, Katingan Hilir, Tasik Payawan and Kamipang Districts showed that 77% of the community agreed, 14% disagreed and 8% were still hesitant.